(untitled) (Research, Society and Development, 2020)
Objective: to present the strategies adopted in the graduation of the health area of ​​a private institution in the Municipality of Rio de Janeiro for the teaching of the discipline of Practice of Health Promotion and Prevention of diseases in the context of the pandemic by COVID-19. Methodology: This is an experience report on remote teaching in undergraduate health at a private institution in the city of Rio de Janeiro, which was designed by two teachers and involved the discipline of health promotion and disease prevention practices, a component the curricular structure of health courses, with the exception of the medical course. Results: The structure of the discipline and its relevance for the training of students, the methodology proposed for teaching during the pandemic of COVID-19 and the strategies adopted by teachers to guide the teaching-learning process and to evaluate the student performance. Conclusion: The willingness of teachers to innovate to make the teaching of undergraduate health care more fluid in the pandemic times of COVID-19 proved to be necessary. In addition to sharing among teachers regarding the development of didactic material and propositional dialogues that involved the discipline, there was a significant effort aimed at building multiple learning strategies in order to generate greater interest, involvement and participation in students.